Right-wing populism and market-fundamentalism: Two mutually reinforcing threats to democracy in the 21st century - Stephan Pühringer; Walter O. Ötsch (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
The article compares market fundamentalism and right-wing populism on the basis of its core patterns of thinking and reasoning. Based on an analysis of the work of important founders of market fundamental economic thinking and the arguments brought forward by leading right-wing populist we find many similarities of these two concepts in their "inner images". Thus, we develop a scheme of the similar dual social worlds of right-wing-populism and market fundamentalism and offer some recent examples of market fundamentalism and right-wing populism mutually reinforcing each other or serving as a gateway for each other. We then apply our scheme for the analysis of the recent political developments and its ideological roots in the US under Donald Trump. The main conclusion of this article is that market fundamentalism and right-wing populism together must be seen as two mutually reinforcing threats to democracy in the 21st century.
Keywords: 330; Right-wing populism; market-fundamentalism; inner images; Donald Trump; patterns of thinking